Progress in The Application of CRISPR-Cas9 Combined With Microbial Engineering - Xing, Xindan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
CRISPR - Cas9 as the third generation of gene editing techniques, widely exists in prokaryotes, and has been widely applied to clinical and pharmaceutical fields. This article reviews the discovery, immune defense process and mechanism of CRISPR-Cas9 and summarizes its application in microbial cells. Advances include achieving gene editing in E. coli, improving defense against phages, and stabilizing chemical production; It is used to modify the characteristics of lactic acid bacteria and precise genome editing in algae; In terms of viruses, it can be used to treat HIV-1 infection, hemoglobinopathy, etc. Research gaps include less research on the effect of optimal length and selective markers of donor DNA homologous arms on efficiency in bacterial gene editing and insufficient evaluation of potential off-target effects and long-term effects of CRISPR/Cas9 systems in algae. This paper mainly analyzed the application of CRISPR-Cas9 in bacteria, lactic acid bacteria, algae, and viruses, and obtained corresponding research results. It provides a theoretical basis and a new idea for the research in the field of microbiology, but there are still some problems to be solved, and future research can focus on optimizing the system, reducing the off-target rate, and improving the editing efficiency.